The Impact of the COVID-19 Pandemic on the Stress Levels of Pregnant Women - Candan Ersanlı; Çağla Yiğitbaş (Genel Tıp Dergisi)

(untitled)
Aim: This study aims to determine the effects of the COVID-19 process on pregnant women in the second and third trimesters, as well as the stress they have experienced and their health behaviors.Material and Methods: The research is of descriptive cross-sectional type. The sample size was calculated using the G*Power program. Necessary permissions were obtained for the research.Due to restrictions in the data collection time period (November 2020-April 2021), 204 participants were reached by convenience sampling method using the online survey tool. A survey form consisting of three parts was used as a data collection tool. Personal information form including questions about sociodemographic characteristics, birth history, pregnancy and pandemic; Pregnancy Stress Rating Scale and Coronavirus Anxiety Scale were employed. High scores on the Pregnancy Stress Rating Scale indicate an increased level of stress during pregnancy. A high score on the Coronavirus Anxiety Scale indicates a high level of anxiety experienced during the coronavirus. In the study, number and percentage values were given, regression and correlation analysis and nonparametric tests were performed.Results: It was found that pregnant women experienced moderate stress during the COVID-19 pandemic, and some obstetric characteristics such as gestational week, having problems in this and previous pregnancies, feeling fear of delivery, and having problems in previous delivery affected stress and COVID-19 anxiety. It has been observed that future anxiety increases in pregnant women who consider the measures taken as inadequate. The mean scores of the scales used in the study are 42.99 ± 24.58 (Min-max: 6-116, median: 40) for Pregnancy Stress Rating Scale, 2.60±3.26 (Min-max: 0-19, median: 2) for Coronavirus Anxiety Scale.Conclusion: The COVID-19 pandemic is one of the factors contributing to increased stress and anxiety in pregnant women.